A fluctuant palatal swelling. (5th June 2014) - Warren, E.; Brady, P.; Sleeman, D.
Abstract: A 78‐year‐old man presented with a fluctuant swelling on the hard palate, which had changed little in the 3–4 years it had been present. Given the nature of the clinical history and presentation, a benign salivary gland neoplasm was thought to be the most plausible diagnosis. Following detailed histological examination of the resected specimen, a definitive diagnosis of myoepithelioma was reached. Although a rarely encountered clinical entity, myoepithelioma should be considered when a salivary gland neoplasm is suspected. Diagnosis can only be made on evaluation of histological features necessitating biopsy in such cases.